Tourism and regional ethnography as a means of social adaptation and integration of children with special needs - Zhyrak L.M (Kharkov National Pedagogical University, 2011)
The notion of child disability, social adaptation and integration, tourism and regional ethnography for children with special needs is considered. The analysis of publications of Ukrainian and foreign scientists dedicated to the problem of child disability and the study of tourism as an important means of adaptation are presented. The features of children with disabilities, the role of physical activity in the process of improving their psychophysical state are studied. The functions, tasks, the influence of tourism on the harmonious development of children with special needs and adapt its conditions of social life are defined.